Novel endoscopic ultrasonography imaging technique for visualizing microcirculation without contrast enhancement in subepithelial lesions: Prospective study. Issue 6 (23rd December 2020) - Yamashita, Yasunobu; Yoshikawa, Takanori; Kawaji, Yuki; Tamura, Takashi; Hatamaru, Keiichi; Itonaga, Masahiro; Ida, Yoshiyuki; Maekita, Takao; Iguchi, Mikitaka; Murata, Shin?ichi; Kitano, Masayuki
Abstract : Objectives: Detective flow imaging for endoscopic ultrasonography (DFI?EUS) is a new imaging modality developed for detecting fine vessels without using ultrasound contrast agents. This study aimed to evaluate its utility by comparing it with a type of directional power Doppler (eFLOW) for subepithelial lesions (SELs). Methods: Between January 2019 and January 2020, 28 patients with SELs undergoing DFI?EUS and eFLOW?EUS were enrolled. DFI?EUS and eFLOW?EUS assessing the vascularity in SELs were compared in terms of the rates of identification of intratumoral vessels. We also investigated how large vessels were depicted in both modalities based on surgical specimens as well as the detection rates of intratumoral vessels in gastrointestinal stromal tumors (GISTs) and non?GISTs using either DFI?EUS or eFLOW?EUS. Results: Among 28 patients, 23 with pathological confirmation by EUS?guided fine?needle aspiration biopsy (EUS?FNAB) specimens were included. Of those 23 patients, the 10 who underwent surgical resection were selected for analysis. The rate of detection of intratumoral vessels in SELs was significantly higher on DFI?EUS (80%) than on eFLOW?EUS (30%) ( P 0=00.03). Comparison with surgical specimens revealed that detection rate for vessels with maximum size of less 10000μm was higher in DFI?EUS (66%) than that in eFLOW?EUS (0%). GIST patients had significantly higher positive rates (90%) of intratumoral vessels than non?GIST patients (31%) on DFI in 23 cases including EUS?FNAB specimens ( P 0=00.045). Conclusions: Detective flow imaging?EUS is more sensitive for depicting intratumoral vessels than eFLOW?EUS. Evaluation of intratumoral vessels on DFI?EUS is useful for identifying GISTs without contrast agents.